2014
DOI: 10.1128/jvi.03824-13
|View full text |Cite
|
Sign up to set email alerts
|

Core Binding Factor Beta Plays a Critical Role by Facilitating the Assembly of the Vif-Cullin 5 E3 Ubiquitin Ligase

Abstract: The HIV-1 virion infectivity factor (Vif) targets the cellular cytidine deaminases APOBEC3G (A3G) and APOBEC3F (A3F) for degradation via the host ubiquitin-proteasome pathway. Vif recruits a cellular E3 ubiquitin ligase to polyubiquitinate A3G/F. The activity of Vif critically depends on the cellular core binding factor beta (CBF␤). In this study, we investigated the Vif-CBF␤ interaction and the role of CBF␤ in the E3 ligase assembly. Vif-CBF␤ interaction requires an extensive region of Vif spanning most of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 41 publications
8
46
1
1
Order By: Relevance
“…Recent studies have shown that the transcription cofactor core-binding factor subunit beta (CBF-␤) is a key factor in Vif function (29,30). CBF-␤ interacts with HIV-1 Vif to enhance Vif's biosynthesis and facilitate Vif folding and stability, thereby enhancing the nucleation of the E3 ubiquitin ligase complex, promoting A3G degradation, and supporting viral infectivity (31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…Recent studies have shown that the transcription cofactor core-binding factor subunit beta (CBF-␤) is a key factor in Vif function (29,30). CBF-␤ interacts with HIV-1 Vif to enhance Vif's biosynthesis and facilitate Vif folding and stability, thereby enhancing the nucleation of the E3 ubiquitin ligase complex, promoting A3G degradation, and supporting viral infectivity (31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…While intrinsically disordered proteins can generally fold independently of chaperon assistance (44,45), recruitment of these molecular chaperoning factors can facilitate particular interactions. In support of this notion, recent biochemical and structural studies indicated that the disordered viral accessory Vif protein recruits cellular core-binding-factor-␤ (CBF-␤; a transcription cofactor known to form functional complexes with the RUNX family of transcription factors [46]), mainly as a molecular chaperon that increases Vif stability and solubility and induces a specific Vif-conformation mandatory for its interaction with cullin-5 and consequent Vif-E3 ligase assembly (47)(48)(49)(50)(51).…”
Section: Molecular Basis Underlying Flexible Exploitation Of Cellularmentioning
confidence: 94%
“…To tag the APOBEC3 restriction factors for proteasomal degradation, HIV-1 Vif (ϳ50% of Vif-host interactions are within the ubiquitylation and proteosome degradation pathway [9]) provides a particularly well-investigated example in which it exploits the E3-ligase complex to evade the APOBEC3 innate im-munity restriction (9,(66)(67)(68)(69). The E3-ligase complex (CRL5) is assembled by Vif and comprises cullin-5 and Elongin B/C and in humans and rhesus macaque crucially requires CBF-␤ for APOBEC3 degradation (50,66,(70)(71)(72) (Fig. 2).…”
Section: Case Study: Cbf-␤ Is Dispensable For Non-primate Lentiviral mentioning
confidence: 99%
“…These lentiviral Vif proteins have evolved to use different strategies for overcoming their host's APOBEC3 (7,38,39,75). HIV-1 Vif assembles the CRL5 E3 ubiquitin ligase to induce the polyubiquitination and proteasome-mediated degradation of APOBEC3 (17,30,(76)(77)(78)(79)(80); this assembly is regulated by CBF␤ (14,(23)(24)(25)(26)(27)(28)39). In contrast, BIV Vif assembles with the CRL2 E3 ubiquitin ligase to induce the polyubiquitination and proteasome-mediated degradation of bovine APOBEC3, and BIV Vif activity is not regulated by CBF␤ (7,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 vif gene encodes a 23-kDa protein of 192 amino acids that counteracts host antiviral factors, the apolipoprotein B mRNA-editing catalytic polypeptide-like 3 (APOBEC3) family cytidine deaminases, by recruiting host cullin-5 (Cul5)-elonginB/elonginC (CRL5) E3 ubiquitin ligase to induce APOBEC3 polyubiquitination, followed by proteasome-mediated degradation in virus-producing cells (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). HIV-1 Vif function is regulated by the transcriptional factor CBF␤ (14,18,(23)(24)(25)(26)(27)(28)(29)(30). When Vif is absent from HIV-1, the host's antiviral APOBEC3 proteins can be packaged into viral progeny and induce lethal mutation in the viruses (13,(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%